2005
DOI: 10.1128/mcb.25.3.979-987.2005
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of Rho and Rac Signaling to the Actin Cytoskeleton by Paxillin during Drosophila Development

Abstract: Paxillin is a prominent focal adhesion docking protein that regulates cell adhesion and migration. Although numerous paxillin-binding proteins have been identified and paxillin is required for normal embryogenesis, the precise mechanism by which paxillin functions in vivo has not yet been determined. We identified an ortholog of mammalian paxillin in Drosophila (Dpax) and have undertaken a genetic analysis of paxillin function during development. Overexpression of Dpax disrupted leg and wing development, sugge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
57
0

Year Published

2005
2005
2009
2009

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 58 publications
(61 citation statements)
references
References 48 publications
4
57
0
Order By: Relevance
“…1A). 8 To identify additional components of the paxillin-mediated signaling pathway, we conducted a misexpression screen for genes that can suppress the dPax-induced wing defects. In a screen of approximately 1,500 independent EP insertion lines (transposable elements), three lines were identified that significantly suppress the frequency and severity of dPax-induced wing blisters.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…1A). 8 To identify additional components of the paxillin-mediated signaling pathway, we conducted a misexpression screen for genes that can suppress the dPax-induced wing defects. In a screen of approximately 1,500 independent EP insertion lines (transposable elements), three lines were identified that significantly suppress the frequency and severity of dPax-induced wing blisters.…”
Section: Resultsmentioning
confidence: 99%
“…In a screen of approximately 1,500 independent EP insertion lines (transposable elements), three lines were identified that significantly suppress the frequency and severity of dPax-induced wing blisters. 8 One of the lines, EP3348, which strongly suppresses dPax-induced blistered wings, harbors a single transposable element inserted in the 5' untranslated region of the Drosophila dAtg1 gene (Fig. 1A and B).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…LIMK1 is a key downstream effector of the Rho family of small GTPases and is activated by phosphorylation on Thr508 by Rho kinase ROCK, or by Rac-Cdc42 p21-activated kinase (PAK) (Edwards et al, 1999). Recent observations showed that a multiprotein complex containing LIMK1 and its kinase activator PAK can be recruited into the focal adhesion complex by p95PKL-mediated binding to Paxillin (Turner, 2000;Chen et al, 2005), raising the possibility that LIMK1 may be required for A␤-induced actin filament remodeling in focal adhesions. To gain additional insight into the molecular mechanism that leads to neuronal dystrophy in AD, we analyzed the involvement of LIMK1, ADF/ cofilin, and actin cytoskeleton in A␤-induced neuritic dystrophy.…”
Section: Introductionmentioning
confidence: 99%